Impact of previous stroke on outcome after thrombectomy in patients with large vessel occlusion. Issue 9 (December 2019) - Leker, Ronen R; Cohen, Jose E; Horev, Anat; Tanne, David; Orion, David; Raphaeli, Guy; Amsalem, Jacob; Streifler, Jonathan Y; Hallevi, Hen; Bornstein, Natan M; Yaghmour, Nour E; Telman, Gregory; et al.
Background: Many patients with large vessel occlusion (LVO) who are otherwise candidates for endovascular treatment (EVT) have had previous strokes. We aimed to examine the effect of previous stroke on outcome after EVT. Methods: Consecutive patients with LVO were prospectively entered into a National Acute Stroke registry of patients undergoing EVT. Patients treated with EVT were divided into those with and without previous strokes. The rates of favorable reperfusion status, mortality, and excellent outcome at 90 days post-stroke as well as symptomatic intracranial hemorrhage (sICH) were evaluated. Results: A total of 390 underwent EVT and 35 had previous strokes. Patients with previous strokes were significantly older; more frequently had a history of prior myocardial infarction and more often had pre-existing functional disability. Favorable target vessel recanalization was less frequently achieved in patients with previous strokes (60% vs. 82%; p = 0.005) and ordinal regression analysis for functional outcome revealed higher frequency of deterioration at three months in patients with previous strokes. Nevertheless, 9% of these patients maintained their previous disability state and sICH rates did not differ between the groups. Mortality rates at one year post stroke were significantly higher in patients with previous strokes (37% vs. 16%; p = 0.005). Conclusions: Previous strokes are associated with higher likelihoods of mortality and unfavorable outcome in patients with LVO undergoing EVT. However, because some of these patients maintain their previous disability state, the presence of previous stroke should not be used as an exclusion criterion from EVT.